Direct and Maternal Genetic Trends for Some Productive and Reproductive Traits in Egyptian Buffaloes - Ibrahim Abu El- Naser (Jurnal Ilmu Ternak dan Veteriner, 2020)
This study was done to determine the direct and maternal genetic and phenotypic trends for productive traits such as first lactation milk yield (FLMY, kg), first lactation period (FLP, d) and first lactation daily milk (FLDM, kg), and reproductive traits such as age at first calving (AFC, mo), First days open (FDO, d) and first calving interval (FCI, d). Data were collected over consecutive 25 years (1991 to 2015) of 1104 first lactation of 135 sires and 482 dams maintained at Mahallet Mousa farms of Animal Production Research Institute. Data were analyzed by Animal model to determine genetic parameters for studied traits. Means of FLMY, FLP, FLDM, AFC, FDO and FCI were 1546.5kg, 189d, 7.9kg, 37.9mo, 120.8d and 428d, respectively. The direct heritability (h2a) for same traits were 0.25, 0.18, 0.24, 0.45, 0.18 and 0.19, respectively. Corresponding maternal heritability (h2m) for mentioned traits was 0.12, 0.19, 0.22, 0.25, 0.12 and 0.12, respectively. Genetic correlations (rg) among studied traits were varied between -0.19 to 0.38. Accuracy of predicted breeding value varied between 69 to 94, 0.37 to 94 and 42 to 91% for FLMY, FLP, FLDM, AFC, FDO and FCI of sires, cows and dams, respectively that revealed the genetic improvement could be actualized through each of cows or sires or dams. Additive and maternal genetic, permanent environmental and phenotypic trends were not significant for all studied traits. It indicated that it is important to set up a plan to improve genetic and environmental conditions thus, increasing productivity and realization of high profitability.